Oceanic mercury concentrations on both sides of the Strait of Gibraltar decreased between 1989 and 2012. (March 2020) - Cossa, Daniel; Knoery, Joël; Boye, Marie; Marusczak, Nicolas; Thomas, Bastien; Courau, Philippe; Sprovieri, Francesca
Graphical abstract: Highlights: Hg concentrations in water columns have been determined both sides of the Gibraltar Strait ∼20 years apart (1989–2012). The decrease is around 30 and 50 % in WMDW and NEACW, respectively. Hg concentrations did not change in the deepest waters of the Atlantic Ocean. Abstract: Mercury (Hg) is a toxic metal that threatens the health of aquatic ecosystems and fish consumers. Its natural cycle has been deeply perturbed by Anthropogenic Hg emissions have deeply perturbed its natural cycle, especially since the start of the Industrial Revolution circa 1850 CE. Anthropogenic Hg emissions from North America and Europe have decreased by a factor of two in the last decades following the implementation of strict regulations. The response of North Atlantic Ocean and Mediterranean waters to this decrease remains poorly documented by field observations. A comparison of results obtained between 1989 and 2012 shows a significant decrease of Hg concentrations in waters on both sides of the Strait of Gibraltar. West of Gibraltar, the Hg decrease ranges from ∼35 % in the upper North East Atlantic Deep Water to ∼50 % in the North East Atlantic Central Water. East of Gibraltar, the observed decrease is ∼30 % in the Western Mediterranean Deep Water. No decrease is observed in the deep Atlantic Ocean layer that formed before the industrial era. These results strongly substantiate the effectiveness of global anti-pollution policies on Hg contamination in oceanic waters. A consequent decline of Hg bioaccumulation in Northeastern Atlantic and Western Mediterranean pelagic ecosystems still requires verification.